The church as a moral agent: In dialogue with Bram van de Beek - Vorster, J. M. (HTS teologiese studies, 2018)
The latter part of the 20th century is known for a surge in the so-called ‘genitive theologies’. Usually, a genitive theology has an ulterior motive, aiming at the transformation of a society or the promotion of sound politics and economy. In recent years, this trend culminated in public theology. The issue of religion with an ulterior motive was raised by Van de Beek in a seminal article focusing on theology without gaining anything from it as an answer to the surging genitive theologies of the latter part of the 20th century and the public theologies of today. Taking into account Van de Beek’s critique against ‘religion with an ulterior motive’, this article explores the concept of the church as a moral agent in dialogue with Van de Beek. The central theoretical argument of this investigation is that Van de Beek’s ecclesiology is valuable when defining the role of the church as a moral agent. However, the perspective of the Kingdom of God concerning the church can enrich one’s views and can add value to his valid critique on public theology.